Caracterização fenotípica e genotípica de Trichosporon spp. implicados em infecções em humanos: um patógeno emergente - Raquel Maria Lima Lemes (2004)
Sixty-five samples of yeasts were analyzed, and 39 were confirmed as belonging to the genus Trichosporon, for the classic method and five excluded by genotyping, through the method of RAPD (Randomly Amplified Polymorphic DNA) for the oligonucleotides use, capable to differentiate the main species of the genus for the characterization of the area of ITS (Intergenic Space). The primer OPA2 made possible the identification of 4 species (T. asahii, T. asteroids, T. ovoides and T. mucoides). The profile of susceptibility of the analyzed samples was tested to six antifungic drugs: amphotericin B (Ampho B), 5-flucitosin (5-Fc), fluconazole (Flu), itraconazoel (Itra), terbinafine (Terb) and voriconazole (Vor), in agreement with the technique described by NCCLS (National Commitee for Control Laboratory Standard) and the method E-test. Trichosporon asahii and T. ovoides presented sensibility at 5-flucitosin, T. mucoides to Ampho B and to Vor, while T. asteroides demonstrated resistance the all of the tested drugs, except for Flu. MIC (minimum inhibitor concentration) for Terb varied from 0.031 – 8.0 mg/mL. All of the species presented resistance to Itra and sensibility to Flu (MIC90 48 hours). The sample of environmental origin and those isolated of superficial and systemic mycoses were sensitive to Ampho B, 5-Fc and Vor, while those originating from of cutaneous and subcutaneous mycoses presented resistance to the polienic drug. All of the samples presented resistance to Itra. Except for two of T. asahii (an isolated from subcutaneous infection and another of superficial), the others presented sensibility to Flu. The comparison among the results obtained by the method of NCCLS and E-test revealed larger discrepancies among the tests with 5-Fc and Itra. RAPD overcame the classic method in the identification of species of Trichosporon, necessary identification to aid to address to the treatment of the trichosporonosis, due to the variability of the susceptibility profile to the antifungals among the species, independent of the isolation site.